Sublingual tacrolimus administration provides similar drug exposure to per‐oral route employing lower doses in liver transplantation: a pilot study. Issue 9 (6th March 2017) - Solari, S.; Cancino, A.; Wolff, R.; Norero, B.; Vargas, J. I.; Barrera, F.; Guerra, J. F.; Martínez, J.; Jarufe, N.; Soza, A.; Arrese, M.; Benitez, C.
Summary: Background: Per‐oral tacrolimus administration is not always practicable. Sublingual administration is a potential alternative, but its feasibility and effectiveness compared with oral route has not been established. Aim: To compare tacrolimus drug exposure after sublingual and oral administration in liver transplant recipients. Methods: Experimental, open‐label, non‐randomised, cross‐over study. Tacrolimus exposure was evaluated in 32 liver transplant recipients receiving oral administration. 12 h tacrolimus area‐under‐the‐curve (AUC0–12 h ) was calculated using tacrolimus blood concentrations at 0‐0.5‐1‐2‐4‐6‐8‐12 hrs post‐dose. Recipients were switched to sublingual administration, and dose was adjusted to reach similar trough levels, new AUC0‐12 h was calculated. Correlation between AUC0‐12 h and trough levels was determined for both oral and sublingual phases. Results: Similar trough levels were accomplished with oral and sublingual administration (6.68 ± 2 ng/mL vs. 6.62 ± 1.9 ng/mL ( P = 0.8)). Although concentration 2 h post dose was higher in oral phase (15.36 ± 7.14 vs. 13.18 ± 5.64, P = 0.015), AUC0‐12 h was similar in both phases (116.6 ± 34.6 vs. 111.5 ± 36.93 ng/mL* h, P = 0.19). Daily dose of tacrolimus required in sublingual phase was 37% lower than that used in oral phase ( P < 0.0001), suggesting significantly increased bioavailability of tacrolimus when employing sublingual route. Good correlation between AUC0‐12 h and trough levels was observed in sublingual phase ( r 2 = 0.74). Twenty‐two recipients were maintained on sublingual administration after the end of study (mean follow‐up: 18.7 ± 5.8 months). No difference in liver function tests or rejection rates was found during follow‐up period. Conclusions: Sublingual administration of tacrolimus is feasible and provides similar drug exposure compared with oral administration. In our study, at long‐term follow‐up, sublingual administration was not associated with liver transplant rejection. Abstract : Linked Content This article is linked to Srinivas, Benitez et al, and O'Leary et al papers. To view these articles visithttps://doi.org/10.1111/apt.14089, https://doi.org/10.1111/apt.14087, andhttps://doi.org/10.1111/apt.14103 .